2014
DOI: 10.1016/j.plaphy.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced glutamine synthetase activity plays a role in control of photosynthetic responses to high light in barley leaves

Abstract: a b s t r a c tThe chloroplastic glutamine synthetase (GS, EC 6.3.1.2) activity was previously shown to be the limiting step of photorespiratory pathway. In our experiment, we examined the photosynthetic high-light responses of the GS2-mutant of barley (Hordeum vulgare L.) with reduced GS activity, in comparison to wild type (WT). The biophysical methods based on slow and fast chlorophyll fluorescence induction, P700 absorbance, and gas exchange measurements were employed. Despite the GS2 plants had high basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…/ P700 total at graduated light intensities (Fig. 2a, b), which can reliably detect any shift of balance between PSs (Zivcak et al 2013;Brestic et al 2014). While in WT, we can see the symmetrical accumulation of Q À A in PSII Photosynth Res acceptor side and P700 ?…”
Section: Imbalance Between Psii and Psi And Its Functional Consequencesmentioning
confidence: 76%
“…/ P700 total at graduated light intensities (Fig. 2a, b), which can reliably detect any shift of balance between PSs (Zivcak et al 2013;Brestic et al 2014). While in WT, we can see the symmetrical accumulation of Q À A in PSII Photosynth Res acceptor side and P700 ?…”
Section: Imbalance Between Psii and Psi And Its Functional Consequencesmentioning
confidence: 76%
“…The PSII as the heart of the photosynthetic process is highly sensitive to the environmental stresses. Its activity could be determined with one non-invasive time-resolved fluorescence measurement, which could measure the polyphasic rise with the basic steps of OJIP [43,[48][49][50][51][52][53][54]. Several studies have shown that the chlorophyll a transient has become one of the most popular tools to estimate stress-induced changes in photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%
“…non-photochemical quenching of chlorophyll fluorescence) is a feedback regulatory mechanism induced upon exposure to high irradiance exceeding that which may be used at maximum quantum yield by photosystem II (PSII) [20,[22][23][24][25][26]. Previous studies have shown that low irradiance protects the photosynthetic apparatus from the adverse effects of high temperature, while photoinhibition protects against both high irradiance and high temperature stress [7,27,28].…”
Section: Introductionmentioning
confidence: 99%